Answer:
Explanation:
This is the formula for the average rate of change
over the interval (a, b)
a and b are x values
f(a) ad f(b) think of them as y values
Start calculating f(a) and f(b) a=1 b=6
replace all x's in formula with a, (1)
f(1)=1³-9(1) = 1-9= -8 f(1) = -8
Now do : b (6)
f(6) = 6³ - 9 (6) = 216-54=162 f(6) = 162
now plug everything into your equation
average rate of change.
notice the 162 - (-8) In math there is no subtraction, and you would change it to + and when you do that you much change the sign of the next value making -8 a +8.
Hope this helps. Good luck!